Sraffa and the Reconstruction of Economic Theory: Volume Three : Sraffa's Legacy: Interpretations and Historical Perspectives - Levrero, Enrico Sergio; Palumbo, Antonella; Stirati, Antonella; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2013)
This book accounts for the work done around the two central aspects of Piero Sraffa's contribution to economic analysis, namely the criticism of the neoclassical theory of value and distribution and the construction of economic theory along the lines of the Classical approach.
Keywords: Economic history; Economic theory; Microeconomics; Macroeconomics; Economics; Microeconomics; Methodology/History of Economic Thought; Economic Theory/Quantitative Economics/Mathematical Methods; Economic History; Macroeconomics/Monetary Economics//Financial Economics